The Influence of Prudence, CEO Gender and CEO Tenure on Earnings Management: In Audit Committee Moderation - Hariyani, Diyah Santi; Nining Rahmawati; Rollis Ayu Ditasari (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
This study aims to empirically prove the effect of prudence, CEO gender and CEO tenure on earnings management with the audit committee as a moderating variable. The research method used is quantitative research with secondary data sources. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange in 2020-2023 with a sample size of 102 companies. The data analysis technique used was Moderated Regression Analysis (MRA) with SPSS 25. The results of the study indicate that prudence has a significant positive effect on earnings management. CEO gender has a significant negative effect on earnings management and CEO tenure has a significant negative effect on earnings management. The audit committee was unable to moderate the effect of prudence on earnings management. However, the audit committee was able to moderate the effect of CEO gender and CEO tenure on earnings management. This study is expected to add insight into how prudence, CEO gender and CEO tenure affect earnings management with the audit committee as a moderating variable. This study makes a significant contribution to understanding the dynamics of corporate governance and the quality of financial reporting. Keywords: Accounting Conservatism; CEO Gender; CEO Tenure; Earnings Management; Prudence